Intrafollicular growth differentiation factor 9: bone morphogenetic 15 ratio determines litter size in mammals†. Issue 5 (29th January 2019) - Christoforou, Efthimia R; Pitman, Janet L
Abstract: We previously showed that rat, pig, sheep, and red deer oocytes express species-specific ratios of GDF9: BMP15 mRNA (3.7, 0.5, 1.26, and 0.1, respectively), and with the exception of the pig, they are directly correlated to litter size. The purpose of this study was to determine the alternative mechanism that enables pig oocytes to secrete low ratios whilst maintaining a large litter size. Herein, we performed same- and cross-species coincubations of oocytes with granulosa cells (GCs) of rat, pig, sheep, and red deer to compare the proliferation rate, mRNA expression levels of growth factor receptors, and downstream signalling pathways in GCs. A decreased proliferation rate, lower Bmpr1b and Bmpr2 mRNA expression levels, and higher SMAD1/5/8 protein levels were exhibited in rat GCs cocultured with red deer oocytes, compared to all other species. Pig GCs unequivocally expressed GDF9 mRNA, suggesting that, similar to rat GCs, the proliferation of pig GCs is regulated mainly by GDF9, despite lower intraoocyte expression of GDF9 mRNA. In support, a higher basal proliferation, and their ability to proliferate readily when coincubated with red deer oocytes, was observed in pig GCs. In contrast, red deer GC proliferation is likely to be mainly regulated by BMP15 in vivo with only red deer oocytes capable of altering SMAD1/5/8 and pSMAD2/3 levels, while both GDF9 and BMP15 appear important for sheep GC proliferation. In summary, this study strengthens our hypothesis that the ratio of GDF9: BMP15 in the intrafollicular milieu is directly correlated with litter size, and that the GCs of each species have evolved to respond to these unique ratios. Abstract : Species-specific responsiveness to and ratios of GDF9: BMP15 determines the litter size in mammals.